Gabonese Republic Report on Growth and Employment : Paving the Way toward Inclusive Growth - World Bank (Washington, DC, 2015)
In 2009 the Gabonese authorities defined a new vision whose strategic guidelines are detailed in an operational plan, the strategic plan for an emerging Gabon (PSGE) whose goal is to turn Gabon into an emerging country within one generation. PSGE includes an ambitious public investment program to develop basic infrastructure and to create the necessary economic environment for the emergence of a diversified economy. The major challenge for PSGE, and how it can be different from previous development plans, will be to become a growth model that is both sustainable and inclusive, leading to a significant improvement in the revenue and living conditions of all Gabonese people. This report is a contribution to the debate on how to achieve this goal. It was developed as part of the implementation of a new World Bank intervention strategy in Gabon wherein competitiveness and employment is the first pillar. It identifies the main obstacles to the low impact of economic growth on employment in Gabon and makes recommendations that will foster dialogue between the World Bank and the Gabonese authorities on the subject. The report is divided into three parts: (i) an analysis of Gabons economic performance since the independence and its effect on employment, (ii) an analysis of the main characteristics of the labor market, and (iii) a review of the main obstacles to job creation. The conclusion recommends some options for reforming the labor market as well as the legal and institutional framework for employment promotion in Gabon.